ANALISIS PERANAN DANA ZAKAT PRODUKTIF TERHADAP PERKEMBANGAN USAHA MIKRO MUSTAHIK (PENERIMA ZAKAT) (Studi Kasus Rumah Zakat Kota Semarang) - Sintha Dwi Wulansari; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2014)
Economic development in Indonesia is an important agenda for every country. SME sector is always described as having a very important role, because SMEs can absorb workers with low education and living in a small business activities, both traditional and modern . The majority of SMEs is the lack of capital ownership, which micro-entrepreneurs do not have sufficient working capital to develop the business .Methods of this study using a descriptive method to determine the system of collection, management and empowerment at the Rumah Zakat zakat funds Semarang. To analyze the effect of the zakat fund productive capital , turnover and profit / income from operations used different test methods ( Paired T -test ) . Objects in this study are given mustahik capital assistance by the Zakat by 30 respondents .From the research results show that Independent Smile program is a program of the venture capital assistance grants or qardhul hasan method . Different test analysis results indicate that the influence of oemberian capital assistance to the development of capital , turnover and profit before and after receiving venture capital assistance .